ActiveMonitor : um método para monitoramento ativo de serviços - Santos, Wagner Laras dos (2012)
Organizations are working cooperatively to achieve common business goals. Service-oriented computing (SOC) is a new approach that provides an infrastructure for the execution of business processes, which are composed of a sequence of activities that must be performed to achieve a business goal. Electronic services are consumed as activities of business processes. They have quality of service (QoS) attributes that must be respected, such as response time or availability of a service. An electronic contract is an electronic document established between service provider and consumer organizations, formalizing agreements (SLAs) that define the minimum QoS that must be met. Service monitoring is an important activity for organizations to be aware of the compliance or non-compliance of SLAs. It uses the terms defined in the contract as parameters for service evaluation. Autonomic computing is an approach to designing computer systems self-managing, which aims to decrease the human involvement. This work is part of Product Line for Business Process Management (PL4BPM) approach that is based on reuse techniques for business processes as principle, and has its focus on monitoring QoS. To enable active monitoring of services, an extension PL4BPM's architecture was proposed. This dissertation presents a method, called ActiveMonitor, which aims at achieving an active monitoring of services through the principles of autonomic computing. The ActiveMonitor was evaluated through an application example using domainspecific metrics in a hypothetical scenario. A prototype that performs one of the main activities defined by the proposed method, the prioritization of customers, was implemented. The use of a Web service by clients with different needs for maximum response time was simulated. The method ActiveMonitor proved to be efficient, especially in situations where demand Web service is near of service provider capacity, making the prioritization of customers and increasing the percentage of compliance with the SLA. An extension to PL4BPM's architecture to allow active monitoring of services was also proposed.